1996
DOI: 10.1038/bjc.1996.499
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tumour burden on chemotherapy-induced nausea and vomiting

Abstract: Summary We investigated how residual tumour burden after cytoreductive surgery was related to the occurrence of acute and delayed nausea and vomiting in 101 ovarian cancer patients receiving their first chemotherapy course. The anti-emetic treatment included ondansetron combined with dexamethasone or placebo. After chemotherapy all patients received ondansetron only for 5 days. Two categories of tumour burden (TB) were formed according to the diameter of the greatest residual tumour (<2 cm = minimal TB and > 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…Ranchor et al reported that high neuroticism was associated with higher levels of distress in both short-and long-term adaptation to cancer [26]. Hursti et al reported low neuroticism to be a predictor of no delayed emesis [15]. As for fatigue, only one study of mixed cancer patients has explored the association between fatigue and neuroticism [31].…”
Section: Discussionmentioning
confidence: 97%
“…Ranchor et al reported that high neuroticism was associated with higher levels of distress in both short-and long-term adaptation to cancer [26]. Hursti et al reported low neuroticism to be a predictor of no delayed emesis [15]. As for fatigue, only one study of mixed cancer patients has explored the association between fatigue and neuroticism [31].…”
Section: Discussionmentioning
confidence: 97%
“…Another explanation for the high rates of nausea in our study could be that the recurrent cancer itself contributes to the nausea. In women with recurrent ovarian cancer, chemotherapy-induced nausea may be further complicated by the presence of peritoneal or liver involvement that may cause additional nausea via direct mechanical effects on the gut, or via stimulation of biological responses (e.g., cytokines, prostaglandins) that may systemically activate the GBA [63]. This study cannot distinguish between these possible mechanistic pathways, however, it is important to note that the presence of cancer per se does not explain the variability in nausea in our sample; 42% of women with active disease were not experiencing nausea.…”
Section: Discussionmentioning
confidence: 99%
“…These factors have been confirmed by multivariate analysis in large, well‐controlled trials, although they have not been assessed prospectively (level of evidence II) 1,9 , 10 . Other factors that are less consistently found in trials but that may be predictive are: (i) younger age, (ii) tumour burden, (iii) low social functioning and (iv) high fatigue scores (level of evidence III) 13 . The clinical application of patient‐related risk factors is somewhat limited.…”
Section: Resultsmentioning
confidence: 99%